Partial Characterization of Crude Protease Extracted from Bacillus amyloliquefaciens NRRL B-14396 - W., Novita; Arief, K.; Nisa, F. C.; Mardiyatmo, U. (Jurnal Teknologi Pertanian, 2006)
This research was aimed to determine the characteristics of crude proteases extracted from Bacillus amyloliquefaciens NRRL B-14396, namely the stability of enzyme during storage at low temperature, the optimum pH and temperature, kinetic constants (Vm and Km) and some inhibitors and activators that influence the enzyme activity and to evaluate the stability of enzyme during storage at low temperature. The results showed that the stability of protease extracted from Bacillus amyloliquefaciens NRRL B-14396 decreased with time when stored at 4oC. It was found two classes of protease, i.e. the one with an optimum pH of 7.5, classified as the neutral protease, and that with the optimum pH of 9.0, known as alkaline protease. The activity levels of the neutral and alkaline proteases were 0.475 Unit/ml and 0.410 Unit/ml, respectively. The optimum temperature was 50oC, at which the activity level was of 0.516 Unit/ml. Ca2+ ion functions as a stabilizer whereas Zn2+ and Fe2+ ions as activators. The addition Mg2+ ion, SDS, and EDTA inhibited the activity. The respective values of Km and Vm of the neutral protease were 0.167% and 0.633 Unit/ml, while those values of the alkaline protease were 0.661% and 0.924 Unit/ml. Key words: characterization, protease, Bacillus amyloliquefaciens.